New Discoveries with Mice Mutant in Endothelial and Platelet Selectins - Hartwell, Daqing W.; Wagner, Denisa D. (Thrombosis and Haemostasis, 1999)
The selectin family of adhesion receptors consists of three members: P-, E-, and L-selectin. P-selectin is constitutively present in the α-granules of platelets and Weibel-Palade bodies of endothelial cells and is rapidly translocated to the cell surface upon activation. E-selectin is synthesized and expressed by activated endothelial cells, whereas L-selectin is constitutively expressed by leukocytes. All three selectins support the rolling of leukocytes on endothelium, which is a prerequisite to firm adhesion and extravasation of leukocytes mediated by integrins and members of the immunoglobulin superfamily.1,2 More recently, it has been demonstrated that P- and E-selectin also support platelet rolling in venules, which will be discussed below. In addition, P-selectin expressed on the surface of activated platelets also mediates platelet-leukocyte adhesion.3,4Since the discovery of the selectins, considerable efforts have been devoted to uncover the functions of these molecules. The development of genetically engineered animals deficient in one or more of the adhesion receptors has provided a unique opportunity and an alternative approach to antibody-blocking experiments for defining the contribution of each of the molecules in normal physiology and pathological conditions. At this time, mice deficient in a single selectin, all combinations of two of the selectins, and all three selectins have been produced by gene targeting.5-10 In this chapter, we will discuss some of the recent findings obtained using mice deficient in P-selectin alone (P-/-), both P- and E-selectin (P/E-/-), and mice expressing Pselectin with a deleted cytoplasmic domain (ΔCT).